2011
DOI: 10.1167/10.1.7
|View full text |Cite
|
Sign up to set email alerts
|

The face-in-the-crowd effect: When angry faces are just cross(es)

Abstract: A common theme running through much of the visual recognition literature is that faces are special. Many studies now describe evidence for the idea that faces are processed in a dedicated center in cortex. Studies have also argued for the presence of evolutionarily expedient pathways dedicated to the processing of certain facial expressions. Evidence for this proposal comes largely from visual search tasks which have established that threatening expressions are more rapidly detected than other expressions: the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
71
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 45 publications
10
71
1
1
Order By: Relevance
“…Indeed, a great debate has long divided psychologists (e.g., Coelho, Cloete, & Wallis, 2010;Goffaux & Rossion, 2006): What is really processed when attention is directed toward a face in general, or an emotional face in particular: the local features or the face as a whole? Arguments in favor of both sides coexist (e.g., Calvo & Nummenmaa, 2008;Horstmann, Becker, Bergmann, & Burghaus, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a great debate has long divided psychologists (e.g., Coelho, Cloete, & Wallis, 2010;Goffaux & Rossion, 2006): What is really processed when attention is directed toward a face in general, or an emotional face in particular: the local features or the face as a whole? Arguments in favor of both sides coexist (e.g., Calvo & Nummenmaa, 2008;Horstmann, Becker, Bergmann, & Burghaus, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…All the nonaffect, low-level feature models for the pseudo-ASE provide that a facial surround is necessary to obtain the effect. Two of the nonaffect models postulate that a pseudo-ASE is due to an absolute advantage for angry features that comes about because of an interaction between the outward pointing eyebrow and mouth features with the facial surround (Calvo & Nummenmaa, 2008;Coelho et al, 2010). Calvo and Nummenmaa argue that the facial surround renders the angry features as being more distinctive, relative to happy and neutral features.…”
Section: Discussionmentioning
confidence: 99%
“…There are equally plausible alternative explanations, however. The schematic face effect may to be due to low-level features that are unrelated to facial affect, but that give an advantage to angry features (Calvo & Nummenmaa, 2008;Coelho et al, 2010). Alternatively,…”
Section: Discussionmentioning
confidence: 99%
“…First, binding effects could be more important for angry voices than happy voices. Indeed, several experiments showed that anger, as a threat-related stimulus, more easily captured attention than happiness did (e.g., Coelho, Cloete, & Wallis, 2010;Ohman, Lundqvist, & Esteves, 2001;Pinkham, Griffin, Baron, Sasson, & Gur, 2010;Weymar et al 2011), an effect called anger superiority effect (Hansen & Hansen, 1988). Moreover, flashbulb memories, which are rated as more negative in valence than everyday memories (Talarico & Rubin, 2003), tended to be more consistently remembered when they were negative than when they were positive (Kensinger & Schacter, 2006).…”
Section: Experiments 1a and 1bmentioning
confidence: 99%